RESPON VARIETAS KUBIS (Brassica oleraceae) DATARAN RENDAH TERHADAP PEMBERIAN BERBAGAI JENIS MULSA - Ramli Ramli (Universitas Tadulako, 2010)
The experiment was conducted at Rindau Countryside, Province of Central Sulawesi which has elevations about 150 m above sea level. Average daily temperature was about 22 – 290C. The objective of the research was to on condition of Central Sulawesi lowland climate (Palu) through the application og mulch the treatment mulch. The experimental design was 5 x 3 factorials design with 2 factors which were arranged in Randomized Block Design with 3 replications. The first factor was variety which is consisted of KK-Cross, Grand 11, Intani, KS-Cross, Galaxi. The second factor was mulch which is consisted of unmulches, straw mulch, black-silver plastic mulch. There was response of both treatments between variety and mulch on plant growth which it can be see on crop growth rate at age 20 - 40 day after planting. However, there was no response of the two treatments at 50 days after planting. Treatment of straw mulch and black-silver plastic mulch can not increase crop fresh weight. The best of crop fresh weight was KS-Cross variety ( 43 ton ha-1) and unmulch treatment is of 40 ton ha-1. The result was higher than the average result of mean of lowland varieties which was only about 4 - 31 ton ha-1